A comparison of the antianhedonic effects of repeated ketamine infusions in melancholic and non-melancholic depression - Zheng, Wei; Yang, Xin-Hu; Gu, Li-Mei; Tan, Jian-Qiang; Zhou, Yan-Ling; Wang, Cheng-Yu; Ning, Yu-Ping (Frontiers in Psychiatry, 2022)
Objectives: Melancholic depression may respond differently to certain treatments. The aim of this study was to compare the antianhedonic effects of six intravenous injections of 0.5 mg/kg ketamine in patients with melancholic and nonmelancholic depression, which remain largely unknown. Methods: Individuals experiencing melancholic (n=30) and nonmelancholic (n=105) depression were recruited and assessed for anhedonic symptoms using the Montgomery–Åsberg Depression Rating Scale (MADRS). The presence of melancholic depression was measured with the depression scale items at baseline based on DSM-5 criteria. Results: A total of 30 (22.2%) patients with depression fulfilled the DSM-5 criteria for melancholic depression. Patients with melancholic depression had a nonsignificant lower antianhedonic response (43.3% versus 50.5%, t=0.5, p>0.05) and remission (20.0% versus 21.0%, t=0.01, p>0.05) to repeated-dose ketamine infusions than those with nonmelancholic depression. The melancholic group had significantly lower MADRS anhedonia subscale scores than the nonmelancholic group at day 26 (p<0.05). Conclusion: After six ketamine infusions, the improvement of anhedonic symptoms was found in both patients with melancholic and nonmelancholic depression, and the efficacy was similar in both groups.